Ontogenetic and inter-elemental osteohistological variability in the leopard tortoise Stigmochelys pardalis - Botha,Alexander Edward; Botha,Jennifer (PeerJ, 2019)
Testudines are a group of reptiles characterized by the presence of a shell covered by keratinous shields. Stigmochelys pardalis is the most widely distributed terrestrial testudine in southern Africa. Although relatively common with some life history traits being well known, the growth of this species has yet to be studied in any detail. The bone microanatomy of this clade differs from that found in other amniotes, where terrestrial species tend to display characteristics normally seen in aquatic species and vice versa. A detailed histological analysis of the limb bones of S. pardalis reveals extensive variation through ontogeny. Cortical bone becomes increasingly thicker through ontogeny and is finally resorbed in the late sub-adult stage, resulting in a thin cortex and a large infilled medullary cavity. The predominant bone tissues are parallel-fibred and lamellar-zonal for the forelimbs and hind limbs respectively. The oldest individual displayed an External Fundamental System indicating that the growth rate had decreased substantially by this stage. Variability is prevalent between the forelimb and hind limb as well as between early and late sub-adults Forelimb elements exhibit characteristics such as faster growing parallel-fibered bone tissue, slightly higher vascularization and a predominance of annuli over Lines of Arrested Growth (LAG) compared to the hind limb which exhibits poorly vascularized, slower growing lamellar-zonal bone interrupted by LAGs. These differences indicate that the forelimb grew more rapidly than the hind limb, possibly due to the method of locomotion seen in terrestrial species. The extensive bone resorption that occurs from the early sub-adult stage destroys much of the primary cortex and results in a significantly different ratio of inner and outer bone diameter (p = 3.59 × 10−5; df = 28.04) as well as compactness (p = 2.91 × 10−5; df = 31.27) between early and late sub-adults. The extensive bone resorption seen also destroys the ecological signal and infers an aquatic lifestyle for this species despite it being clearly terrestrial. This supports the results of other studies that have found that using bone microanatomy to determine lifestyle in testudines does not produce accurate results.
Keywords: Testudines; Osteohistology; Microanatomy; Ontogenetic variability; Inter-elemental variability; Ecological signal; Lifestyle